The effect of special training to develop the combat efficiency of elite men in special operations (Journal of the College of Basic Education, 2022)
Preparing a curriculum for special training for elite men in special operations, and identifying the impact of the training curriculum on developing combat competence, and the researcher used the experimental method in his study. Fighters were divided into two groups, control and experimental, and pre-exams were conducted at (9) in the morning.